2020
DOI: 10.4049/immunohorizons.2000002
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 and TLR8 Differentially Activate the IRF and NF-κB Pathways in Specific Cell Types to Promote Inflammation

Abstract: TLR7 and TLR8 are pattern recognition receptors that reside in the endosome and are activated by ssRNA molecules. TLR7 and TLR8 are normally part of the antiviral defense response, but they have also been implicated as drivers of autoimmune diseases such as lupus. The receptors have slightly different ligand-binding specificities and cellular expression patterns that suggest they have nonredundant specialized roles. How the roles of TLR7 and TLR8 differ may be determined by which cell types express each TLR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 41 publications
5
100
0
Order By: Relevance
“…It has been observed that plasmacytoid dendritic cells (pDCs), B cells, and monocytes express TLR7. At the same time, TLR8 is expressed by myeloid DC (mDC) and macrophages in humans [ 89 ]. TLR7 has been shown to detect single-stranded RNA (ssRNA), polyuridine, as well as synthetic ssRNA rich in uridine along with guanosine [ 90 ].…”
Section: Activation Of the Innate Immune Systemmentioning
confidence: 99%
“…It has been observed that plasmacytoid dendritic cells (pDCs), B cells, and monocytes express TLR7. At the same time, TLR8 is expressed by myeloid DC (mDC) and macrophages in humans [ 89 ]. TLR7 has been shown to detect single-stranded RNA (ssRNA), polyuridine, as well as synthetic ssRNA rich in uridine along with guanosine [ 90 ].…”
Section: Activation Of the Innate Immune Systemmentioning
confidence: 99%
“…Cq is currently studied in multiple clinical trials, either in monotherapy (ChiCTR2000029609) or in combination with other drugs such as remdesivir . Similarly, Hq sulfate (a less toxic derivate of Cq) also displays an activity spectrum which includes coronaviruses, in addition to its immunomodulatory potential through the inhibition of TLR7, 8 signalling and the suppression of TNF-a and IL6 synthesis (Picot et al, 1993;Jang et al, 2006;Bender et al, 2020). These therapeutic molecules showed an additional effect during both the entry and post-entry stages of SARS-CoV-2, as was also shown in Vero E6 cells, and were included in March 2020 in the Chinese guidelines for the management of COVID-19 (Vincent et al, 2005;Yao et al, 2020).…”
Section: Endocytosis Inhibition Hydroxychloroquine a Controversial Drugmentioning
confidence: 99%
“…Remdesivir is an adenosine analogue which also controls mTORC1 signalling and has a wide spectrum against coronaviruses including resistant strains (Sheahan et al, 2017;Agostini et al, 2018). Remdesivir has shown in vitro activity against SARS-CoV-2 in combination with chloroquine or in monotherapy, as part of a 10-day intravenous treatment in COVID-19 patients with severe pneumonia (Adaptive COVID-19 Treatment Trial ACTT-NCT04280705) (Beigel et al, 2020). Moreover, the intravenous use of remdesivir on a compassionate-use basis to patients with SARS-CoV-2 infection receiving oxygen support, has been associated with a clinical improvement in 68% of patients, according to a study published in April by Grein et al (2020).…”
Section: Drugs Targeting Post-entry Stepsmentioning
confidence: 99%
See 2 more Smart Citations